2014
DOI: 10.1051/0004-6361/201322958
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a stellar disk into a boxy bulge: The outside-in part of the Milky Way bulge formation

Abstract: By means of idealized, dissipationless N-body simulations that follow the formation and subsequent buckling of a stellar bar, we study the characteristics of boxy/peanut-shaped bulges and compare them with the properties of the stellar populations in the Milky Way (MW) bulge. The main results of our modeling, valid for the general family of boxy/peanut shaped bulges, are the following: (i) Because of the spatial redistribution in the disk initiated at the epoch of bar formation, stars from the innermost region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
120
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(137 citation statements)
references
References 84 publications
17
120
0
Order By: Relevance
“…This scenario has recently been examined by Di Matteo et al (2014), who argued that the characteristics (kinematics, chemistry) of the metal-poor bulge component agree better with a thick-disk nature than with a spheroid. In particular, they argued that a classical bulge spheroid with the mean metallicity of ARGOS C cannot be larger than 10 8 M (Gallazzi et al 2005), which is incompatible with the number of stars in that component.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario has recently been examined by Di Matteo et al (2014), who argued that the characteristics (kinematics, chemistry) of the metal-poor bulge component agree better with a thick-disk nature than with a spheroid. In particular, they argued that a classical bulge spheroid with the mean metallicity of ARGOS C cannot be larger than 10 8 M (Gallazzi et al 2005), which is incompatible with the number of stars in that component.…”
Section: Discussionmentioning
confidence: 99%
“…Thick disks, however, are found to be ubiquitous, and are detected on nearly all nearby edge-on disks galaxies (Comerón et al 2011). Recent results (Ness et al 2013a,b;Di Matteo et al 2014 have confirmed the view that the Milky Way (MW) is also a pure disk galaxy (Shen et al 2010;Kunder et al 2012), i.e., it has no substantial classical bulge. Furthermore, measurements of its SFH have shown that during the peak of star formation in the universe, the MW was a star-bursting galaxy and was forming its thick disk (Snaith et al , 2015Lehnert et al 2014).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, measurements of its SFH have shown that during the peak of star formation in the universe, the MW was a star-bursting galaxy and was forming its thick disk (Snaith et al , 2015Lehnert et al 2014). The structural parameters of this population, with a short scale length (Bensby et al 2011;Cheng et al 2012a;Bovy et al 2012) suggest that it constitutes most of the mass in the MW's central region (Ness et al 2013a,b;Di Matteo et al 2014Haywood et al, in prep. ).…”
Section: Introductionmentioning
confidence: 99%
“…These data show that different populations overlap in the inner region of the Milky Way, and at moderate latitudes their component C has metallicity, alpha abundances, and velocities very similar to the old thick disc we found, while component B could be a counterpart of our younger thick disc. Most recently, Di Matteo et al (2014) analysed simulations of the bulge evolution and showed that components B and C identified by ARGOS survey can also be identified with the young and old thick discs. A more detailed analysis of the metallicity and velocities distributions in the inner region with newly available spectroscopic surveys will be performed in the near future using the new population model proposed here.…”
Section: Thick Disc In the Inner Galaxymentioning
confidence: 99%